Implementation of Communicative and Interactive Method in Strengthening Students' Speaking Skills through English Club Activities at MTs Muslimat NU Palangka Raya - Siliwangi, Diah Puji; Erliana, Santi (Jurnal Pengabdian Sosial, 2025)
This article discusses about community service activity that aims to implement communicative and interactive methods as an effort to strengthen students' speaking skills through English Club activities at MTs Muslimat NU Palangka Raya. This activity is designed to provide a more active and enjoyable learning experience and provide space for students to practice using English more naturally outside of formal learning. The activity is carried out through several stages, starting from an introduction to the activity, mentoring during animal-themed "Puzzle Games", compiling descriptive texts, and presenting short presentations in front of the group. During the activity, students showed high enthusiasm, became more confident in speaking, and were able to convey simple descriptions with greater confidence. The interactive and collaborative atmosphere created made students more comfortable and engaged in every stage of learning. The implementation results show that communicative and interactive methods are effective in helping strengthen students' speaking skills through a creative and relaxed learning approach. This activity is expected to be an alternative for ongoing mentoring in developing English language skills in the school's extracurricular environment. Thus, the implementation of communicative and interactive methods has been proven to have a positive effect on strengthening students' speaking skills and can be used as a strategy for developing English language learning in the Madrasah environment.